Teachers' Quality in Learning Process Amid Covid-19 Pandemic: Factors That Explain Professional Educators - Hery Setiyo Nugroho (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the quality of teachers in the learning process during the COVID-19 pandemic as a factor that describes professional educators. This study used a cross-sectional design. Participants were taken randomly from one of the private universities in Palembang. The participants were 120 people. Data were taken from questionnaires, teaching documents owned by teachers and also a literature review. The data analysis technique used is the percentage technique and cross-tabulation. The results show that the quality of teachers must have several aspects so that the implementation of teaching and learning during the covid-19 pandemic goes well and can achieve educational goals. As for the quality teaching aspect of the findings of this study, the quality of teachers from the findings of this study must carry out professional development, in-service training, pre-service training, teacher leadership, policies and partnerships, teacher curriculum training, and teaching management, and teacher qualifications. The results of the study have implications for the understanding of teachers to improve personal abilities to fulfil the components of quality teachers.